The literature as tariqa: Muhammad Iqbal’s thought between European Modernity and Islamic Tradition - de Diego González, Antonio (Anales del Seminario de Historia de la Filosofía, 2022)
Muhammad Iqbal is the most important Islamic philosopher of the contemporary Indian Subcontinent. In his extensive work there is a deep dialogue between the Philosophy of European modernity (Hegel, Goethe, Nietzsche), Islamic tradition (Rumi and Sufism) and Indian Philosophy (Bartrihari, Guru Nanak) that always leads him to spiritual transcendence. The aim of this paper is, in a transversal methodology and for the first time in Spanish, to show that tension through his intellectual and literary production, emphasizing how this became his tariqa (spiritual path).
Keywords: Indian Philosophy; islam; european modernity; Iqbal; Metaphysics; Philosophy of Religion